4-3(t+2)+t=5(t-1)-7t

Simplify each term.

Apply the distributive property.

4-3t-3⋅2+t=5(t-1)-7t

Multiply -3 by 2.

4-3t-6+t=5(t-1)-7t

4-3t-6+t=5(t-1)-7t

Simplify by adding terms.

Subtract 6 from 4.

-3t-2+t=5(t-1)-7t

Add -3t and t.

-2t-2=5(t-1)-7t

-2t-2=5(t-1)-7t

-2t-2=5(t-1)-7t

Simplify each term.

Apply the distributive property.

-2t-2=5t+5⋅-1-7t

Multiply 5 by -1.

-2t-2=5t-5-7t

-2t-2=5t-5-7t

Subtract 7t from 5t.

-2t-2=-2t-5

-2t-2=-2t-5

Add 2t to both sides of the equation.

-2t-2+2t=-5

Combine the opposite terms in -2t-2+2t.

Add -2t and 2t.

0-2=-5

Subtract 2 from 0.

-2=-5

-2=-5

-2=-5

Since -2≠-5, there are no solutions.

No solution

Solve for t 4-3(t+2)+t=5(t-1)-7t